Politik Lokal di Bangka Belitung: Antara Timah dan Etnis Tionghoa - Rakhmad Kavin (Institut Pemerintahan Dalam Negeri (IPDN), 2016)
Political transformation in Indonesia in 1998, have an impact on the local administration, the whole society can participate to determine the direction of local development. Local political upheaval in Bangka Belitung province can not be separated from the natural resources of Tin became one of the sources of income of local communities and also Local revenue sources and also can not be separated from Chinese ethnic who is an ethnic with the second largest population after Malay ethnic who live and interact in the region of Bangka Belitung. This study illustrates how natural resources of Tin and Ethnic Thionghoa dyeing conditions local politics.